2009
DOI: 10.1097/pcc.0b013e3181ae5c1a
|View full text |Cite
|
Sign up to set email alerts
|

An explorative study on quality of life and psychological and cognitive function in pediatric survivors of septic shock

Abstract: In this group of septic shock survivors, health-related quality of life, anxiety, and depression are equal to or slightly better than the age-related Dutch norm population. Cognitive function is decreased, especially in children admitted at younger ages. Follow-up studies with adequate neuropsychological testing are warranted to evaluate the association between septic shock, cognitive function, and risk factors for cognitive problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 45 publications
3
54
0
2
Order By: Relevance
“…One other study reported worse cognitive functioning in children who survived septic shock, but in this study only self-reports were used (19). Elison et al (20) found a specific deficit for pattern recognition memory in their study with three MSS children aged 6 to 12 yrs old, 3 to 7 months after discharge.…”
Section: Cognitive Functioningmentioning
confidence: 95%
“…One other study reported worse cognitive functioning in children who survived septic shock, but in this study only self-reports were used (19). Elison et al (20) found a specific deficit for pattern recognition memory in their study with three MSS children aged 6 to 12 yrs old, 3 to 7 months after discharge.…”
Section: Cognitive Functioningmentioning
confidence: 95%
“…Discrepancies may be related to differences in inclusion criteria; length of follow-up; and use or not of healthy controls. Cognitive sequelae have been identified in sub-groups of acutely ill children, including meningitis (16)(17)(18)(19), sepsis or septic shock (7,20,21), and meningococcal disease (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Severe sepsis and septic shock are major healthcare problems that affect millions of people around the world each year, killing one in four compromised people (Dellinger et al 2013b). Besides this elevated mortality, several studies have demonstrated that sepsis survivors present long-term impairment in cognition, including changes in memory, attention, concentration and/or global cognitive decline (Bronner et al 2009;Hopkins et al 2004;Iwashyna et al 2010;Jackson et al 2011;Rothenhausler et al 2001).…”
Section: Introductionmentioning
confidence: 99%